2019
DOI: 10.1111/ene.13953
|View full text |Cite
|
Sign up to set email alerts
|

Conduction block in immune‐mediated neuropathy: paranodopathy versus axonopathy

Abstract: Background and purpose Conduction block is a pathognomonic feature of immune‐mediated neuropathies. The aim of this study was to advance understanding of pathophysiology and conduction block in chronic inflammatory demyelinating polyneuropathy (CIDP) and multifocal motor neuropathy (MMN). Methods A multimodal approach was used, incorporating clinical phenotyping, neurophysiology, immunohistochemistry and structural assessments. Results Of 49 CIDP and 14 MMN patients, 25% and 79% had median nerve forearm block,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
(43 reference statements)
4
10
1
Order By: Relevance
“…This can be the result of various cellular mechanisms, such as demyelination or a disturbance of the cytoskeleton caused by a loss of neurofilaments and microtubules. We think that our findings may reflect demyelination rather than a disturbance of the cytoskeleton as histological studies reported myelin detachment The mechanism of paranodal myelin detachment is present in some patients with CIDP, as described in earlier electrophysiological studies [42][43][44]. Taken together, the changes in FA, MD and RD in our CIDP group most likely reflect the loss of myelin.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This can be the result of various cellular mechanisms, such as demyelination or a disturbance of the cytoskeleton caused by a loss of neurofilaments and microtubules. We think that our findings may reflect demyelination rather than a disturbance of the cytoskeleton as histological studies reported myelin detachment The mechanism of paranodal myelin detachment is present in some patients with CIDP, as described in earlier electrophysiological studies [42][43][44]. Taken together, the changes in FA, MD and RD in our CIDP group most likely reflect the loss of myelin.…”
Section: Discussionsupporting
confidence: 75%
“…We think that our findings may reflect demyelination rather than a disturbance of the cytoskeleton as histological studies reported myelin detachment and myelin loss without damage to axons induced by macrophages around the (inter)nodal regions in patients with CIDP [ 3 , 4 , 5 , 38 , 39 , 40 , 41 ]. The mechanism of paranodal myelin detachment is present in some patients with CIDP, as described in earlier electrophysiological studies [ 42 , 43 , 44 ]. Taken together, the changes in FA, MD and RD in our CIDP group most likely reflect the loss of myelin.…”
Section: Discussionmentioning
confidence: 81%
“…Nerve excitability studies in CIDP suggest disruption of nodal sodium-channel function and resulting hyperpolarisation may interfere with nerve conduction and cause block (Cappelen-Smith et al 2000, 2001Boerio et al 2010;Lin et al 2011). Elevated thresholds on nerve excitability studies have also been demonstrated in CIDP patients with and without conduction block compared to healthy controls, possibly related to changes in the paranodal region (Garg et al 2019). Although autoantibodies are only identified in a minority of patients (Devaux et al 2016), it is hypothesized that IVIg competes with functionally important autoantibodies, producing rapid although reversible improvement in nodal function (Boerio et al 2010;Berger et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Depolarisation at the site of CB may result in this observation via intracellular sodium (Na + ) accumulation possibly due to sodium channel or Na + /potassium (K + )-pump dysfunction. Recent mathematical modelling by Garg and colleagues suggested reductions of Na + and K + ion channel function along the axon distal to CB 24. These functional disturbances of the axonal membrane have been hypothesised to lead to increased ectopic generation manifesting as positive symptomatology such as fasciculations and cramps 23.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Using indirect immunofluorescence on rat teased nerve fibres incubated with sera of 11 MMN patients, Garg et al identified only one patient with a paranodal staining pattern despite 55% of patients being anti-GM1 IgM positive 24. In contrast, 9 of 11 CIDP patients with CB showed staining at the node, paranode and/or myelin.…”
Section: Pathophysiologymentioning
confidence: 99%